Riverine microplastic contamination in southwest Germany: A large-scale survey - Schrank, Isabella; Löder, Martin G. J.; Imhof, Hannes K.; Moses, Sonya R.; Heß, Maren; Schwaiger, Julia; Laforsch, Christian (Frontiers in Earth Science, 2022)
Microplastic (MP) contamination of freshwater ecosystems is still in focus of research and public attention, as aquatic environments have a high ecological, economical, and recreational value. We now know that rivers do not only function as pathways of MPs into oceans but may also act as temporary MP sinks. However, due to methodological differences, the comparability of studies on MP contamination of rivers is still limited. To compare MP contamination between different river systems, to investigate if there are distinct MP distribution patterns with respect to different MP sources and to analyze if there is constant increase in MP contamination from the upper to the lower course of the river, we set up a large-scale survey. We chose two large river systems, the Rhine and Danube catchment with its tributaries, and sampled 23 rivers of different size at 53 sampling locations in Southwest-Germany. Surface water sampling, sample processing and analysis was performed with the same methodology to get comparable results on MP number, polymer type, particle size and shape. Fully quantitative data was generated down to 300 µm by using a manta trawl net with a 300 µm mesh size for sampling. Nevertheless, we also included particles down to a size of 20 µm in our FTIR analysis after plastic-friendly sample purification by enzymatic-oxidative treatment. Plastic concentrations recorded in surface water at the sampling locations ranged from 0.7 to 354.9 particles/m³. With respect to all samples, the amount of particles increased towards lower size classes (61 ± 34.2 % below 300 µm) and fragments were the prevailing shape (90.7 ± 13.6 %). Polyethylene (49.2 ± 25.9 %) and polypropylene (33.2 ± 22.3 %) were the most frequent polymer types. Our survey did not reveal distinct MP distribution patterns nor a constant increase of MP abundance within river course in the investigated river systems. Thus, although providing a large-scale data set, our study shows that sampling MPs representatively is challenging, as MP particles are not homogeneously distributed in rivers. This further indicates that spatial and temporal changes in MP abundance should always be considered in MP monitoring approaches.